An experiment on non-luxury fashion counterfeit purchase: the effects of brand reputation, fashion attributes, and attitudes toward counterfeiting. Issue 2 (March 2018) - Park-Poaps, Haesun; Kang, Jiyun
Abstract The purpose of this experimental study was to investigate the effects of brand reputations (high vs. low), evaluation of product attributes, and attitudes toward counterfeiting on the purchase likelihood of non-luxury counterfeit fashion products (shirts, handbags, shoes). A total of 121 female college students participated in a 2 (counterfeit vs. genuine purchasing situation) × 2 (brand reputation) laboratory experiment. In general, across the product types, effects of purchasing situation were slightly different across products types. Brand reputation was found significant affecting purchase likelihood for shirts and shoes. A pattern of the interaction between the purchase situation and brand reputation was detected, although not statistically significant. The effects of attitudes toward counterfeiting were generally unsupported, while the effects of fashion-related and value attributes were significant across the three products.